Compact Dual-Channel (Hyperspectral and Video) Endoscopy - Cai, Fuhong; Gao, Min; Li, Jingwei; Lu, Wen; Wu, Chengde (Frontiers in Physics, 2020)
The combining of reflected endoscopic imaging with spectral data has recently attracted much attention. In this study, we used an optical fiber bundle probe, a galvo-scanning module and an imaging spectrometer module to realize a dual-channel endoscope that is capable of simultaneously acquiring real-time video data and high-throughput hyperspectral data. The frame per second of the video channel is 30, and the wavelength range in the hyperspectral channel is 400–750 nm, with a 3 nm spectral resolution at 547 nm. To achieve fast hyperspectral imaging, we extracted the region of interest (ROI) from the video channel and utilized it as guidance to drive the galvo-scanning module to obtain the hyperspectral data in the ROI. In this way, the hyperspectral imaging speed for a selected ROI area can be reduced to about 1 second, making it possible to achieve rapid detection. Utilizing this system, we acquired the hyperspectral image of fingerprints, dorsum of the hand, and skin melanin nevus, demonstrating that compact dual-channel endoscopy has broad implications for research and therapeutics.